Live Streaming Of Skincare Products: The Role Of Celebrity Endorses On Impulsive Buying - Ramdani, Luki; Rufaidah, Popy (Universitas Dharma Wacana, 2024)
The purpose of this study is to identify the influence of live streaming and celebrity endorsers on impulse buying among skincare users. This research was conducted to the users of skincare products with a total sample of 130 respondetns using purposive sampling techniques and applying descriptive quantitative-based research methods with data processing involving the use of statistical analysis methods through the SEM-PLS programme. The results of this study reveal that the live streaming variable (? = 0.242 p-value <0.01) has a positive and significant effect on impulse buying among users of the skincare products and celebrity endorsers (? = 0.418, p-value <0.01) have a positive and significant effect on impulse buying among users of the skincare products. Thus,H1 and H2 are accepted. From a theoretical point of view, the results provide a new angle that combines live streaming content and celebrity endorsers in increasing customers' impulse buying, where the more often audiences see, hear, and absorb information about skincare products delivered by celebrities, the more likely they are to make impulse buying